2022
DOI: 10.3389/fmed.2022.793591
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Undergraduate Nursing Students' Academic and Clinical Performance: A Mixed-Methods Study

Abstract: BackgroundThere is conflicting and limited information regarding factors that influence undergraduate nursing students' academic and clinical performance prior to entry to practice.ObjectiveTo identify factors influencing the academic and clinical performance of undergraduate nursing students throughout the course.DesignMixed methods study utilizing a retrospective cohort and a qualitative study.SettingMonash University, Melbourne, Australia.ParticipantsLongitudinal existing data of nursing undergraduate stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It was noted that students with high GPAs showed more dedication to learning by reading in advance, being more responsible, and putting extra effort into practicing nursing skills. Also, those with higher GPAs have a high level of assertiveness [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that students with high GPAs showed more dedication to learning by reading in advance, being more responsible, and putting extra effort into practicing nursing skills. Also, those with higher GPAs have a high level of assertiveness [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may not be a significant concern in most cases, but our analysis demonstrates that third-year students participate in research at significantly higher rates than lower-year-level students. For example, (Fooladi et al, 2022;Song et al, 2014). The highest mark attained by the vast majority of participants was a B or B+, and over half of all participants achieved one of these grades.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors reported that the use of electronic resources increased the students' classroom interest and participation. Fooladi et al (2022) conducted a mixed-methodology study to identify the factors that influence academic and clinical performance of undergraduate nursing students. Students felt that an interactive curriculum helped them to be successful.…”
Section: Discussionmentioning
confidence: 99%